Boc-Val-Val-OMe (Aβ39–40) and Boc-Ile-Ala-OMe (Aβ41–42) crystallize in a parallel β-sheet arrangement but generate a different morphology. Issue 31 (18th July 2018) - Giri, Rajat Subhra; Mandal, Bhubaneswar
Abstract : Crystal structures and morphologies of Boc-Val-Val-OMe (Aβ39–40 ) and Boc-Ile-Ala-OMe (Aβ41–42 ), the two consecutive dipeptides of the C -terminus of Aβ, are reported. Abstract : Both N - and C -protected dipeptides, Boc-Val-Val-OMe (1 ) and Boc-Ile-Ala-OMe (2 ), bearing sequence homogeneity with the C -terminus of Alzheimer's Aβ39–40 and Aβ41–42, respectively, exhibit intermolecular hydrogen-bonded supramolecular parallel β-sheet structures in crystalline form. But the higher order aggregation of2 showed a clear supramolecular cross-β-sheet structure unlike that of1 . FESEM images indicated that, while1 self-assembled into a highly organized two ended spear-like architecture, 2 formed a hollow hexagonal tube-like structure, in a methanol–water solvent mixture. These molecules self-assembled into the ordered structures which found to bind with the amyloid binding dyes thioflavin T (ThT) and Congo red. FT-IR and PXRD also support the formation of the β-sheet structure both in solution and in the solid state. These results may help in understanding amyloidogenesis and design principle of nanostructures.